Pengaruh Media Game Adventure terhadap Higher Order Thinking Skills (HOTS) Siswa pada Mata Pelajaran Informatika Kelas X di SMA - Savira, Intan; Anugrah, Septriyan; Yusri, Meldi Ade Kurnia; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using adventure game media on students' Higher Order Thinking Skills (HOTS) in the Informatics subject for grade X at high school. This study uses a quantitative approach with a quasi-experimental research type. In this study, two classes were used, namely the experimental class and the control class. The research subjects were grade X students of SMA Negeri 1 Singingi, totaling 56 students, with X3 as the experimental class using adventure game media and X1 as the control class using the lecture method. The research instruments used in this study were pretest and posttest questions. The instruments consisted of HOTS tests that measured the aspects of analysis (C4), evaluation (C5), and creation (C6). Data were analyzed using normality tests, homogeneity tests, and t-tests with the assistance of SPSS version 25. The data analysis results obtained a t-count value greater than the t-table, namely 3.827 > 1.674 for the experimental class and 2.827 > 1.674 for the control class. Meanwhile, the significance value (sig. 2-tailed) for higher-order thinking skills (HOTS) is 0.00 < 0.05; therefore, H0 is rejected and Ha is accepted. Thus, it can be concluded that the use of adventure game learning media has a significant effect on students' higher-order thinking skills (HOTS) in Informatics subjects for grade X in high school during the 2025/2026 academic year.